Supershop management Models: An optimised way to manage the supershop using hyperautomation and machine learning - Ahmed, Shuvro; Mojumder, Rajesh; Rahman, MD.Mahmudur; Karmoker, Joy; Fatin, Shadman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.